The benefits of virtual fieldtrips for future-proofing geography teaching and learning. Issue 2 (15th March 2023) - Mercer, Theresa G.; Kythreotis, Andrew P; Harwood, Joseph; Robinson, Zoe P.; George, Sharon M.; Sands, David; Brown, Joshua M.; Sims, Toby
ABSTRACT: This resource paper explores the benefits of developing virtual fieldtrips to help future-proof geography teaching and learning in times of uncertainty and change. Drawing on a case study from a second-year biogeography module that saw cancellations to in-person fieldtrips in the first UK COVID-19 lockdown and the development of a virtual fieldtrip by the third UK COVID-19 lockdown, we offer some insights and lessons learnt to help other academics and practitioners adopt this approach.